Electronic Medical Record (EMR) at Physiotherapy Clinic - Tyas, Zahra Arwananing; Wira Nata Negara; Muhammad Sugiharto Bagus Wijaya; Muhammad Yusuf Nurrohman; Dika Rizki Imania (Universitas 'Aisyiyah Yogyakarta, 2024)
The development of the digital world is accelerating with the presence of the COVID-19 pandemic around the world. The need for digitization is also needed in the health sector, such as EMR (Electronic Medical Records) to facilitate services in recording patient medical data. The Regulation of Physiotherapy Service Standards aims to provide a reference for the implementation of quality and accountable physiotherapy services to improve the quality of physiotherapy services to patients which is one of the technological advances in the industrial revolution 4.0 by providing EMR. With this EMR, it is hoped that it can facilitate physiotherapists' access to medical record data from patients that is neatly structured. EMRs with structured data can also help clinic owners make new decisions based on stored data. This research was conducted by observation, interview, and discussion methods for analysis and design. The results of the discussion and analysis of this study are structured, neat data according to the concept of relational data. 12 Entities generated from structured data and relationships from each entity that connects one to the other consist of 10 relationships. This study resulted in a pilot system for ERM specifically for Physiotherapy Clinics because it has structured and clearly documented data such as database design using ERD (Entity Relational Diagram) and DOD (Data Object Description), as well as system design and display.